Effect of Posterior Tibial Nerve Stimulation on Fecal Incontinence among Geriatrics - Agalya, S.; Kumaresan, Abathsagayam; Santhana Lakshmi, Sivakumar; Surya, Vishnuram; Prathap, Suganthirababu; Vignesh, Srinivasan; Vinodhkumar, Ramalingam; Buvanesh, Annadurai (INTI International University, 2023)
Background and aim: Incontinence is one of the most common causes for admission to a residential facility. Fecal incontinence becomes more prevalent at the age of 70. In both men and women, fecal incontinence is a common condition, particularly among the elderly. Although a few research suggests that posterior tibial nerve stimulation can aid with fecal incontinence, more research is needed. Preoperative and postoperative measures are compared to determine treatment outcomes. Thus, the goal of this research is to see how posterior tibial nerve stimulation affects fecal incontinence in geriatrics. Methods: The research was conducted as a pilot study at SIMATS, using samples taken from Saveetha hospital's neuro IPD and physiotherapy OPD. A total of 15 patients were chosen at random based on the inclusion and exclusion criteria. The research included both geriatric men and women with fecal incontinence who were examined using the Wexner score prior and after intervention. The posterior tibial nerve was stimulated with electrical stimulation twice a day for 4 weeks. Result: The occurrence of incontinent episodes in geriatric individuals was drastically decreased, with a significant value of p<0.001. Conclusion: The use of posterior tibial nerve stimulation in the elderly has been proven to be a successful therapy technique for reducing fecal incontinence episodes. In terms of treatment, the findings of this study seem promising.